Oil Price Fluctuations and Macroeconomy: Empirical Evidence from Egypt, Iran and Saudi Arabia - Voo, Vincent Chung Yin (2009)
This research concludes that the respective macroeconomic performances of Egypt, Iran and Saudi Arabia economy are adversely affected by oil price shocks. Both impulse response and variance decomposition analysis provide reasonable evidence to support that the impact had mixed significant adverse effects on their gross domestic product (GDP) and inflation. Further analysis is conducted to examine these countries past experience of oil shocks. In summary, this study identifies that the impact of an oil price shock on the economies of Egypt and Saudi Arabia is marginal but it is significant for the case of Iran.